2022
DOI: 10.3390/ijms23084376
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulations and Network-Based Profiling of Binding and Allosteric Interactions of SARS-CoV-2 Spike Variant Complexes and the Host Receptor: Dissecting the Mechanistic Effects of the Delta and Omicron Mutations

Abstract: In this study, we combine all-atom MD simulations and comprehensive mutational scanning of S-RBD complexes with the angiotensin-converting enzyme 2 (ACE2) host receptor in the native form as well as the S-RBD Delta and Omicron variants to (a) examine the differences in the dynamic signatures of the S-RBD complexes and (b) identify the critical binding hotspots and sensitivity of the mutational positions. We also examined the differences in allosteric interactions and communications in the S-RBD complexes for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 144 publications
8
15
0
Order By: Relevance
“…The conformational mobility distributions for the Omicron RBD complexes displayed several deep local minima corresponding to residues 374–377 and the RBD core residue cluster (residues 396–403) as well as interfacial RBD positions that are involved in the contacts with the hACE2 receptor (residues 445–456 and 496–505 of the binding interface) ( Figure 2 A). The observed structural stability of the core RBD regions was also seen in our earlier simulation studies of the original RBD Wu-Hu-1 and Omicron complexes [ 64 ], indicating that these segments remain relatively rigid in all Omicron variant complexes with hACE2. Noteworthy, the most stable RBD positions included important hydrophobic stability centers F400, I402, F490, Y453, L455, A475, and Y489 ( Figure 2 A).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The conformational mobility distributions for the Omicron RBD complexes displayed several deep local minima corresponding to residues 374–377 and the RBD core residue cluster (residues 396–403) as well as interfacial RBD positions that are involved in the contacts with the hACE2 receptor (residues 445–456 and 496–505 of the binding interface) ( Figure 2 A). The observed structural stability of the core RBD regions was also seen in our earlier simulation studies of the original RBD Wu-Hu-1 and Omicron complexes [ 64 ], indicating that these segments remain relatively rigid in all Omicron variant complexes with hACE2. Noteworthy, the most stable RBD positions included important hydrophobic stability centers F400, I402, F490, Y453, L455, A475, and Y489 ( Figure 2 A).…”
Section: Resultssupporting
confidence: 76%
“…The study concluded that Omicron BA.2 subvariant may have evolved to maintain ACE2 binding similar to the original strain while promoting more efficient antibody evasion highlighting how a complex pattern of mutations balances these conflicting factors [ 63 ]. By employing the conformational ensembles of the S-RBD Omicron variant complexes with ACE2 we recently performed simulations and mutational scanning of the interfacial RBD residues showing that N501Y is the critical binding affinity hotspot in the S Omicron RBD complex with ACE2, while hotspots Q493R, G496S, Q498R anchor the key interfacial clusters responsible for binding with ACE2 [ 64 ]. By assessing over 700 mutant complexes, the recent study revealed that high-affinity RBD mutations (including N440K, S443A, G476S, E484R, G502P) tend to cluster near known human ACE2 recognition sites supporting the view that combinatorial mutations in SARS-CoV-2 can develop in sites amenable for non-additive enhancements in binding and antibody evasion.…”
Section: Introductionmentioning
confidence: 99%
“…The conformational mobility distributions for the Omicron RBD complexes displayed several deep local minima corresponding to residues 374-377 and the RBD core residue cluster (residues 396-403) as well as interfacial RBD positions that are involved in the contacts with the hACE2 receptor (residues 445-456 and 496-505 of the binding interface) (Figure 2A). The observed structural stability of the core RBD regions was also seen in our earlier simulation studies of the original RBD Wu-Hu-1 and Omicron complexes [65], indicating that these segments remain relatively rigid in all Omicron variant complexes with hACE2. Noteworthy, the most stable RBD positions included important hydrophobic stability centers F400, I402, F490, Y453, L455, A475, and Y489 (Figure 2A).…”
Section: Resultssupporting
confidence: 76%
“…The study concluded that Omicron BA.2 subvariant may have evolved to maintain ACE2 binding similar to the original strain while promoting more efficient antibody evasion highlighting how complex pattern of mutations balances these conflicting factors [64]. By employing the conformational ensembles of the S-RBD Omicron variant complexes with ACE2 we recently performed simulations and mutational scanning of the interfacial RBD residues showing that N501Y is the critical binding affinity hotspot in the S Omicron RBD complex with ACE2, while hotspots Q493R, G496S, Q498R anchor the key interfacial clusters responsible for binding with ACE2 [65]. By assessing over 700 mutant complexes, the recent study revealed that high-affinity RBD mutations (including N440K, S443A, G476S, E484R, G502P) tend to cluster near known human ACE2 recognition sites supporting the view that combinatorial mutations in SARS-CoV-2 can develop in sites amenable for non-additive enhancements in binding and antibody evasion.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of nonadditive, epistatic relationships among RBD mutations was assessed using protein structure modeling by comparing the effects of all single mutants at the RBD–ACE2 interfaces for the Omicron variants, showing that structural constraints on the RBD can curtail the virus evolution for a more complete vaccine and antibody escape [ 78 ]. By employing the conformational ensembles of the S-RBD Omicron variant complexes with ACE2, we recently performed simulations and mutational scanning of the interfacial RBD residues, showing that N501Y is the critical binding affinity hotspot in the S Omicron RBD complex with ACE2, while hotspots Q493R, G496S, and Q498R anchor the key interfacial clusters responsible for binding with ACE2 [ 79 ].…”
Section: Introductionmentioning
confidence: 99%